PERAN KEPALA SEKOLAH RAUDHATUL ATHFAL DALAM MEWUJUDKAN SEKOLAH RAMAH ANAK - Zuri Pamuji (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
Child-friendly Raudhatul Athfal is early childhood education institutions that apply the principles of child protection in the organization of educational process. Those principles are the principles of non-violence and discrimination against children, the principle of the best interests of the child and the rights of child development, and the principles for respect of the child views. The application of these principles will be implemented properly if getting an optimal supported by principals. An optimal supported by the principals in Raudhatul Athfal to apply the principles of child protection can be done in various fields, i.e.: the relations between personnel in daily activities, the management and regualtion of educational institutions,the facilities, infrastructure and environment, the areas of study and thedecision-making and policy.